2022
DOI: 10.1155/2022/5377690
|View full text |Cite
|
Sign up to set email alerts
|

Arisaema heterophyllum Blume Monomer Stigmasterol Targets PPARγ and Inhibits the Viability and Tumorigenicity of Lung Adenocarcinoma Cells NCI-H1975

Abstract: To clarify the regulatory effect and molecular mechanism of Arisaema heterophyllum Blume (AhBl) monomer stigmasterol on lung adenocarcinoma in human lung adenocarcinoma cells NCI-H1975 cultured in vitro and in nude mice. Oil red O staining, free fatty acid detection, adenosine triphosphate (ATP), and NADPH were applied to elucidate the regulatory effect of stigmasterol on the energy metabolism of NCI-H1975 cells. Simultaneously, colony formation assay and nude mouse tumorigenesis were performed to clarify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The study of Song et al. ( 24 ) performed in vivo and in vitro experiments to investigate the regulatory role of stigmasterol in LUAD and try to clarify the corresponding molecular mechanism of action. They found that stigmasterol distinctly inhibited the viability of NCI-H1975 cells but promoted lipid deposition.…”
Section: Role Of Stigmasterol In Different Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Song et al. ( 24 ) performed in vivo and in vitro experiments to investigate the regulatory role of stigmasterol in LUAD and try to clarify the corresponding molecular mechanism of action. They found that stigmasterol distinctly inhibited the viability of NCI-H1975 cells but promoted lipid deposition.…”
Section: Role Of Stigmasterol In Different Cancersmentioning
confidence: 99%
“…Studies have unraveled various biological and pharmaceutical properties of stigmasterol, such as analgesia ( 8 ), anti-inflammation ( 9 14 ), anti-oxidization ( 15 , 16 ), anti-diabetes ( 15 , 17 , 18 ), maintaining psychiatric status ( 19 ), lowering blood cholesterol level ( 20 , 21 ), improving learning and memory ability ( 22 ), and protecting against Leishmania ( 6 ), etc. Moreover, stigmasterol is recently reported with anti-tumor potential either in vivo or in vitro in several cancers (e.g., lung cancer ( 23 , 24 ), liver cancer ( 25 – 27 ), gallbladder cancer ( 28 , 29 ), gastric cancer ( 30 , 31 ), and ovarian cancer ( 32 )) via inhibiting growth while promoting apoptosis in tumor cells ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%